Membrane adsorbers with ultrahigh metal-organic framework loading for high flux separations - Wang, Hang; Zhao, Shuang; Liu, Yi; Yao, Ruxin; Wang, Xiaoqi; Cao, Yuhua; Ma, Dou; Zou, Mingchu; Cao, Anyuan; Feng, Xiao; Wang, Bo (Nature communications, 2019)
Metal-organic frameworks (MOFs) with high porosity and designable functionality make it possible to access the merits of high permeability and selectivity. However, scalable fabrication methods to produce mixed matrix membranes (MMMs) with good flexibility and ultrahigh MOF loading are urgently needed yet largely unmet. Herein, we report a thermally induced phase separation-hot pressing (TIPS-HoP) strategy to roll-to-roll produce 10 distinct MOF-membranes (loadings up to 86 wt%). Ultrahigh-molecular-weight polyethylene interweaving the MOF particles contributes to their mechanical strength. Rejections (99%) of organic dyes with a water flux of 125.7 L m –2 h –1 bar –1 under cross-flow filtration mode. The micron-sized channels between the MOF particles translate into fast water permeation, while the porous MOFs reject solutes through rapid adsorption. This strategy paves ways for developing high-performance membrane adsorbers for crucial separation processes. As a proof-of-concept, the abilities of the membrane adsorbers for separating racemates and proteins have been demonstrated. Mixed matrix membranes have shown great promise for separation applications, but low filler loading typically leads to low selectivity. Here the authors use a thermally induced phase separation-hot-pressing strategy to fabricate 10 distinct metal-organic framework-based membrane adsorbers with up to 86 wt% MOF-loading.